Life ceremony : stories - Murata, Sayaka, 1979- (Grove Press, an imprint of Grove Atlantic, 2022)
"With Life Ceremony, the incomparable Sayaka Murata, whose Convenience Store Woman has now sold more than a million copies worldwide, returns with a brilliant and wonderfully unsettling collection, her most recent fiction to be published in Japan. In these twelve stories, Murata mixes an unusual cocktail of humor and horror and turns the norms and traditions of society on their head to better question them. In "A First-Rate Material," Nana and Naoki are happily engaged, but Naoki can't stand the conventional use of deceased people's bodies for clothing, accessories, and furniture, and a disagreement around this threatens to derail their perfect wedding day. "Lovers on the Breeze" is told from the perspective of a curtain in a child's bedroom that jealously watches the young girl Naoko as she has her first kiss with a boy from her class and does its best to stop her. "Eating the City" explores the strange norms around food and foraging, while "Hatchling" closes the collection with an extraordinary depiction of the fractured personality of someone who tries too hard to fit in. In these strange and wonderful stories of family and friendship, sex and intimacy, belonging and individuality, Murata asks what it means to be a human in a world that often seems very strange, and offers answers that surprise and linger."--